Kansei Engineering Application for Designing Excelsa Wonosalam's Coffee Packaging - Auditya Bisma; Dodyk Pranowo; Yusuf Hendrawan (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Visual packaging attributes such as brand name, logo, color, packaging form, writing style and graphics are used for product identification and affect the buying decision (willing-to-buy). Framework systematic development of Kansei Engineering using Artificial Neural Networks, an imitation of the human brain used to modelling the learning process of customer assessments. This research aims to analyze the development of packaging designs of Excelsa Wonosalam Coffee based on Kansei Engineering. Kansei Engineering is widely used for developing product designs oriented to the Kansei (emotion) of the customer and relating them to product attributes. Data was obtained by conducting surveys of coffee customers and literature studies. The sampling technique used purposive sampling. The packaging design attributes are graphics, color and shape. The combination of Kansei Engineering and Artificial Neural Networks generate packaging design preferences obtained from the modelling of customer assessment of available attributes. Coffee packaging design preferences involve ringin contong graphic, red color, and squircle shape. These design preferences could be a consideration for coffee entrepreneurs for packaging design innovations. This research is expected to provide added value for industry and SMEs to create more attractive designs.